Thermal behaviour of stevensite at temperatures up to 800°C. - Christidis, G. E.; Koutsopoulou, E. (Bulletin of the Geological Society of Greece, 2013)
Stevensite is a Mg-trioctahedral smectite with layer charge stemming from vacancies in the octahedral sheet. In the present work we studied the thermal behavior of Jbel Ghassoul stevensite from Morocco, known as Ghassoulite or Rhassoulite, free of talc layers. The clay fraction of the material was separated by sedimentation, it was subsequently heated from 250° to 800° C and the end products were examined with X-ray diffraction (XRD) and Fourier Transform Infrared (FTIR) spectroscopy. The influence of heating on the stevensite structure begins at 400°C and is completed at 500°C. It involves irreversible collapse of the layers at 10Å, which do not re-expand in ethylene glycol (EG) vapors. In contrast, heating at lower temperatures does not affect the stevensite layers, which expand completely in EG. The FTIR spectra indicate the formation of talc-like (kerolite) layers after heating at temperatures exceeding 400°C. Within the current experimental setup, the transition to kerolite layers takes place without the formation of an intermediate mixed-layer stevensite/talc phase. Heating at higher temperatures does not change the transformation pattern, until 800°C where complete dehydroxylation of the 2:1 layer takes place, which is associated with the formation of enstatite. The results of this study clearly demonstrate that opposite to common trioctahedral and dioctahedral smectites, stevensite converts to another layer silicate prior to dehydroxylation.